Design and fabrication of III-V RF devices for MMIC applications - Ang, Kian Siong (2008)
Submicron AlGaAs/InGaAs Pseudomorphic High Electron Mobility Transistor (PHEMT) grown on GaAs substrate by MBE (Molecular Beam Epitaxy) has been designed, fabricated and characterized in this work.